Game (wildlife) meat safety: understanding the game meat supply chain and the roles of role-players in a multifaceted control environment - Bekker, J. L. (J. Leon), speaker; Renecker, Lyle, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
As in other parts of the world, the South African game industry is expanding and game meat is finding its way in the local and international food supply chain. In order to do effective game meat control, one must have an understanding of the game meat supply chain and the stakeholders therein. The term 'food supply chain' refers to the total supply process from agricultural production, harvest / slaughter, through processing and handling of a food and its ingredients, storage and distribution up to consumption. In the case of game meat, the supply chain will include the relevant food and meat control authorities, primary producers (farmers), suppliers of feed and veterinary drugs to farmers, hunters, abattoirs, small and large scale processors, wholesale and retail, suppliers of processing materials, import and export agencies, transport and the consumer. From this it is clear that several role-players are involved, which leads to a multifaceted and fragmented food control environment. It was necessary to determine the control points essential for meat safety and the responsibilities of the role-players for the execution of these control points along the game meat supply chain. Information regarding the study was obtained through a desk top study and analysis of questionnaire responses from game farmers, hunters and national, provincial and municipal control authorities. Game meat is often entering the supply chain in an uncontrolled manner while there is a lack of a single formal framework for its operation amongst the stakeholders. To address this issue, the research looked for insight into the game meat supply chain; the differences between the game meat supply chain and the conventional meat supply chain; the respective role-players in the supply chain; and the essential meat safety control points along the supply chain. The crucial meat safety link between the supply chain and the roles of stakeholders in ensuring that safe meat is supplied to the consumer is often vague. The introduction of a mechanism to reduce the indistinctness is essential for this growing industry. The mechanism suggested relates to the establishment of a game meat safety forum whereby all role-players are involved.
Moderator: Lyle Renecker.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses